Hydrodynamics and sediment transport on the North Canterbury Shelf, New Zealand - Cowan R. Nokes; Helen C. Bostock; Lorna J. Strachan; Mark G. Hadfield (New Zealand Journal of Marine and Freshwater Research, 2021)
This study uses a combination of regional ocean modelling systems (ROMS), a sediment transport model (sedtrans05) and detailed grainsize data with the aim of determining the hydrodynamics and primary sediment transport pathways on the North Canterbury Shelf (NCS), South Island of New Zealand. Combining the results from the hydrodynamic model, sediment grainsize data and sediment transport model in an unsupervised classification scheme, highlights 5 classes of sediment on the shelf. These classes include a high energy inner shelf with coarse sands and gravels (Class 1), a low to medium energy mid shelf allowing for the deposition of fine sediments in a large depocenter (Class 2 and 3), and an area on the mid to outer shelf of relict coarse sediments (Class 4). With the exception of Class 4, the sediment distribution is in equilibrium with the modern hydrodynamics and validates the ROMS and SedTrans05 models. This understanding of the NCS hydrodynamic and sedimentary system will help with the management of the marine environment, with the caveat that this is a highly dynamic environment which is influenced of earthquakes and large storms influencing erosion, transport and distribution of sediment in this region.

Ocean acidification in New Zealand waters: trends and impacts - Cliff S. Law; James J. Bell; Helen C. Bostock; Chris E. Cornwall; Vonda J. Cummings; Kim Currie; Simon K. Davy; Malindi Gammon; Christopher D. Hepburn; Catriona L. Hurd; Miles Lamare; Sara E. Mikaloff‐Fletcher; et al. (New Zealand Journal of Marine and Freshwater Research, 2018)
The threat posed by ocean acidification (OA) to the diversity and productivity of New Zealand marine ecosystems is assessed in a synthesis of published trends and impacts. A 20‐year time series in Subantarctic water, and a national coastal monitoring programme, provide insight into pH variability, and context for experimental design, modelling and projections. A review of the potential impact of changes in the carbonate system on the major phyla in New Zealand waters confirms international observations that calcifying organisms, and particularly their early life‐history stages, are vulnerable. The synthesis considers ecosystem and socio‐economic impacts, and identifies current knowledge gaps and future research directions, including mechanistic studies of OA sensitivity. Advanced ecosystem models of OA, that incorporate the indirect effects of OA and interactions with other climate stressors, are required for robust projection of the future status of New Zealand marine ecosystems.